Power system stability and control - Kundur, P. (McGraw-Hill, 2014)
Suitable for electric and utility engineers, power system stability and control, written by prabha kundur, comprises of numerous topics on voltage stability, with an aim to present the concepts in a clearer manner. It provides its readers with a generic introduction to the concept of electric power systems, stating its structure, design and operating criteria for stability references. It touches upon both mid-term as well as long-term voltage stability and discusses the problems of power system stability